BIODEGRADATION OF ENDOSULFAN BY ESTUARINE HALOTOLERANT BACTERIUM AND INSINUATION OF TOXICITY TOWARDS ARTEMIA SALINA - V.NEELAMBARI; D.ANNADURAI (International Journal of Pharma and Bio Sciences, 2013)
The study determines the degradation and detoxification potential of cyclodiene insecticide endosulfan by halotolerant bacterial strains. After repeated screening, Streptococcus agalactiae a halotolerant endosulfan degrading bacterium which tolerate upto 5000ppm of endosulfan was isolated from enriched sediment of the Vellar estuary. The bacterium shows maximum growth by 3.8 (cfu 5.2×108) with pH 3.5. Degradation study reveals that the endosulfan degradation efficiency of 40.77% by GCMS analysis with 80% chloride release in the medium. The optimum growth parameters of S. agalactiae for endosulfan degradation was found to be pH-8, 35ËšC, dextrose as carbon source, salinity 30ppt, inoculum size of 100µl/ml or 10ml L-1 broth with 2.5 × 106 cfu/ml under shaking condition with 15days incubation respectively. The 24 hrs LC50 of BSLA study confirm the detoxification of endosulfan by the halotolerant bacterium. The results of the present study concluded this potential strain could be useful in reclamation of any contaminated site in the tropics.